ISOLASI BAKTERI PENDEGRADASI MINYAK MENTAH DAN POLISIKLIK AROMATIK HIDROKARBON DARI SEDIMEN MANGROVE BINTAN - Afianti, Nur Fitriah; Febrian, Deva; Falahudin, Dede (Indonesian Institute of Sciences, 2019)
Isolation of Crude Oil and Polycyclic Aromatic Hydrocarbon-Degrading Bacteria from Mangrove Sediments in Bintan. Bintan is known for its extensive mangrove areas, but it is prone to pollution from oil spills due to it is close to the international shipping lane. Indigenous bacteria plays important roles in bioremediation of oil spills in the natural environment. This research aims to explore indigenous bacteria from Bintan?s mangrove sediments which may have ability to degrade crude oil and polycyclic aromatic hydrocarbon (PAH). The mangrove sediment samples were taken in March 2018 from the sediments near four different mangrove plant species, i.e. Rhizophora apiculata, Xylocarpus granatum, Ceriops tagal and Lumnitzera littorea. Isolation of oil degrading bacteria was carried out using enrichment media supplemented with crude oil ALCO. A total of 45 strains of oil degrading bacteria were successfully isolated from the sediment samples. By using sublimation method, 13 bacterial isolates showed the ability to degrade various PAHs, including phenanthrene, acenaphthene, dibenzothiophene and fluorene. Sequencing analysis of 16s rRNA genes confirmed that the 13 isolated bacteria belong to the genera Rhodococcus, Bacillus, Sphingopyxis, Rhizobium, Mycobacterium, and Gordonia